Análise do custo do ciclo de vida em uma planta de beneficiamento de coprodutos - Soares, Rodolpho Rodrigues (2019)
Cost control of assets has been increasingly important in corporations, as it has become a key competitiveness factor in the markets in which they operate. The purpose of this work is to perform a RAM (Reliability, Availability and Maintenance) analysis to define which asset in a co-product beneficiation plant has an impact on the maximization of production. Another step that is also the scope of this work is to carry out an analysis of the selected asset life cycle cost (LCCA) and define the best strategy to be adopted in the coming years. The analysis pointed to a sieve of coproducts processing demonstrating that the use of the appropriate methodology is necessary for assertive decision making taking into account not only technical and management factors but also the economic life of the asset. The case study was able to show not only which asset has the greatest influence on plant availability, which is the vibrating screen, but also the best strategy to be adopted considering the asset life cycle that is based on the Asset Management standard. As a result of the analysis it was found that the strategy to be adopted is the acquisition of a new sieve and 12 years is the economic life of a new asset considering the current maintenance parameters.